2009
DOI: 10.1590/s1516-31802009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous spinal anesthesia versus combined spinal epidural block for major orthopedic surgery: prospective randomized study

Abstract: CONTEXT AND OBJECTIVES: In major orthopedic surgery of the lower limbs, continuous spinal anesthesia (CSA) and combined spinal epidural anesthesia (CSE) are safe and reliable anesthesia methods. In this prospective randomized clinical study, the blockading properties and side effects of CSA were compared with single interspace CSE, among patients scheduled for major hip or knee surgery. DESIGN AND SETTING:Prospective clinical study conducted at the Institute for Regional Anesthesia, Hospital de Base, São José … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
1
27
2
Order By: Relevance
“…[51213] Clinical studies have shown that hemodynamic stability is greater with CSA than with other neuraxial anesthesia techniques,[123814] but limited studies have been published on this technique for elderly patients. Few studies or case reports[9101516] have evaluated the efficacy and safety of CSA in this population, probably because of concerns about potential adverse effects-principally neurologic complications and PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…[51213] Clinical studies have shown that hemodynamic stability is greater with CSA than with other neuraxial anesthesia techniques,[123814] but limited studies have been published on this technique for elderly patients. Few studies or case reports[9101516] have evaluated the efficacy and safety of CSA in this population, probably because of concerns about potential adverse effects-principally neurologic complications and PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of the effect depends on the position of the patient's body, the type of surgery, the technique of anaesthesia.Severe hypotension is associated with high risk in case of advanced age, therefore the continuous spinal anaesthesia (CSA) is a well-established technique that has been used successfully in this group of patients. CSA is an effective technique in elderly patients undergoing lower extremity surgery (3,14). Imbelloni and co-workers found that the CSA technique compared with the CSE block is safer for high-risk patients with unstable haemodynamics because the injected dose of a local anaesthetic is lower, it gives better control of the level of blockade and shorter duration of arterial hypotension (14).…”
Section: Discussionmentioning
confidence: 99%
“…CSA is an effective technique in elderly patients undergoing lower extremity surgery (3,14). Imbelloni and co-workers found that the CSA technique compared with the CSE block is safer for high-risk patients with unstable haemodynamics because the injected dose of a local anaesthetic is lower, it gives better control of the level of blockade and shorter duration of arterial hypotension (14).…”
Section: Discussionmentioning
confidence: 99%
“…But technical exertion in introduction of spinal catheters occurs, due to the likelihood of complication like Caudal Equina syndrome and Post Dural Puncture Headache (PDPH), thus limiting the technique. [9,10] We did not find any randomized studies in the literature comparing sequential CSEA with unilateral SA for lower limb orthopaedic surgery. The aim of giving unilateral SA is to bound dispersal of spinal block only to the operated side for unilateral lower limb interventions.…”
Section: Discussionmentioning
confidence: 99%